(untitled) (ELang | An English Language Education Journal, 2018)
This paper entitled “The Use of Picture in Teaching The Present Continuous Tense”. It is about use of pictures in teaching verb-ing in present continuos tense. It is written as a partial fulfillment of the requirements for taking Sarjana Pendidikan Degree. This pre-experimental research is done in the eighth grade of SMP Muhammadiyah 6 Baleendah, With df= N-1= 27-1= 26, at p= 0.05 of two tailed, the value of t-table = 2.056. As the derived t is bigger than that of the t-table (2.257>2.056), Ho is rejected and Ha is accepted, stating that there is significant difference in students’ mean scores before and the after the treatment using pictures in the eighth grade of SMP Muhammadiyah 6. The mean of post-test is significantly higher than the mean of pre-test. This means that the picture in teaching the present continuous tense to eight grade of SMP Muhammadiyah 6 is effective. Students of SMP Muhammadiyah 6 Baleendah give a positive response toward use of picture. Therefore the writer concluded that eighth grade of SMP Muhammadiyah 6 Baleendah like learning verb-ing using pictures. Keyword :Picture, Present Continuous